Web-Based Student Admission System Design at Vocational Education of Brawijaya University - Sovia Rosalin (Jurnal VOK@SINDO, 2014)
Internet has been used in all aspects such as in the military, social, business, and education started from elementary school up to university. Nowadays, each university has used internet to convey information fast. At University of Brawijaya, internet also has been used centrally in the process of selection of student admission through the use of web. However, Vocational Education of Brawijaya University has particular criteria for performance assessment in the process of selection of student admission, particularly for those majoring in Banking, Secretary as well as Tourism and Hospitality. Regarding this, it is then necessary to design a student admission system at Vocational Education by using PHP programming language, HTML, CSS, Javascript and MySQL database. This system is expected to ease prospective students to obtain information related to the selection process started from enrollment until admission announcement; ease the head of Vocational Education to get the report related to the result of the selection of student admission; reduce fraud in the selection process; and assist the academic department in processing data related to major preference based on the result of written and performance tests.